The relationship between coping and distress among faculty members and students during COVID-19 pandemic lockdown: The moderating effect of gender - Hamid, Abdalla A. R. M.; Miskry, Abdullah Seif Abdullah Al; Darweesh, Abdel Hameed M. (Frontiers in Psychiatry, 2023)
Objectives: Previous research has documented significant associations between the COVID-19 pandemic lockdown, various mental health problems, and coping strategies. However, literature on the moderating role of gender on the relationship between distress and coping strategies during COVID-19 is almost nonexistent. Hence, the main objective of this study was two folds. To examine gender differences in distress and coping strategies, and to test the moderating effect of gender on the relationship between distress and coping among university faculty members and students during the COVID-19 pandemic. Method: A cross-sectional web-based study design was used to collect data from the participants. A sample of 649 participants (68.9% university students and 31.1% faculty members) was selected. The General Health Questionnaire (GHQ-12) and the Coping Inventory for Stressful Situations (CISS) were used to collect data from the participants. The survey was sent out during the COVID-19 lockdown from May 12th to June 30th, 2020. Results: The results showed significant gender differences in distress and the three coping strategies. Women consistently scored higher on distress (P < 0.01), task-focused (P < 0.05), emotion-focused (P < 0.001), and avoidance coping (P < 0.01) compared to men. Gender moderated the relationship between emotion-focused coping and distress (P < 0.001) but not the relationship between distress and task-focused or avoidance coping. Conclusion: Increased emotion-focused coping is associated with decreased distress among women while the use of emotion-focused coping by men predicted more distress. Workshops and programs focused on providing skills and techniques on how to cope with stressful situations induced by the COVID-19 pandemic are recommended.